Reduced tonic inhibition in striatal output neurons from Huntington mice due to loss of astrocytic GABA release through GAT-3 - Wójtowicz, Anna M.; Dvorzhak, Anton; Semtner, Marcus; Grantyn, Rosemarie (Frontiers in Neural Circuits, 2013)
The extracellular concentration of the two main neurotransmitters glutamate and GABA is low but not negligible which enables a number of tonic actions. The effects of ambient GABA vary in a region-, cell-type and age-dependent manner and can serve as indicators of disease-related alterations. Here we explored the tonic inhibitory actions of GABA in Huntington's disease (HD). HD is a devastating neurodegenerative disorder caused by a mutation in the huntingtin gene. Whole cell patch clamp recordings from striatal output neurons (SONs) in slices from adult wild type mice and two mouse models of HD (Z_Q175_KI homozygotes or R6/2 heterozygotes) revealed an HD-related reduction of the GABA(A) receptor-mediated tonic chloride current (ITonic(GABA)) along with signs of reduced GABA(B) receptor-mediated presynaptic depression of synaptic GABA release. About half of ITonic(GABA) depended on tetrodotoxin-sensitive synaptic GABA release, but the remaining current was still lower in HD. Both in WT and HD, ITonic(GABA) was more prominent during the first four hours after preparing the slices, when astrocytes but not neurons exhibited a transient depolarization. All further tests were performed within 1 to 4 h in vitro. Experiments with SNAP5114, a blocker of the astrocytic GABA transporter GAT-3, suggest that in WT but not HD GAT-3 operated in the releasing mode. Application of a transportable substrate for glutamate transporters (D-aspartate 0.1 - 1 mM) restored the non-synaptic GABA release in slices from HD mice. ITonic(GABA) was also rescued by applying the hyperagonist gaboxadol (0.33 µM). The results lead to the hypothesis that lesion-induced astrocyte depolarization facilitates nonsynaptic release of GABA through GAT-3. However, the capacity of depolarized astrocytes to provide GABA for tonic inhibition is strongly reduced in HD.